On GP-InjectivityWith Some Types of Rings - Abdullah M. Abdul-Jabbar; Raida D. Mahmood (College of Education for Pure Sciences, 2007)
Abstract The purpose of this paper is to study GP-injective modules and give some of it is properties. Also, we proved: (1) If every simple right R-module is GP-injective, and R is reversible ring, then R is a right weakly -regular. (2) Let R be a right weakly regular, right quasi-duo ring, if every simple singular right R-module are GP-injective, then R is -regular.